Levantamento etnodirigido em dois municípios da região sul do Tocantins, Brasil - Silva, Rafaianny Milhomem da (Universidade Federal do Tocantins, 2018)
Ethnodirigid surveys report the knowledge of medicinal plants used by local populations from generation to generation. The objective of the research was to sculpt the popular understanding regarding the use and method of preparation of the plants used in popular medicine in the counties of Talismã and Gurupi located in the southern region of the state of Tocantins. Fifty semistructured questionnaires were applied to individuals aged 20 to 89 by the snowball methodology until sample exhaustion, with the female gender being the most representative. One hundred and six (106) plants were identified in the survey, totaling 42 families, especially the Lamiaceae family. The most frequently cited plant in both cities was Mentha piperita and the most commonly used plant was the leaf in the town of Gurupi and the bark in Talisman. The results contribute to the knowledge of the medicinal plants used in the studied region and so that new surveys are carried out for a better profiling of the regional plants and their use.